(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Children considered as one third of today’s population and the whole future for us. For raising society being healthy, it is vital of having children being healthy. Mechanical airway obstruction is a communal and fatal fortune in group of pediatric age. It needs prompt treatment and recognition for avoiding outcomes as fatal. Despite aspiration of foreign body (FBA) could be event as threatening of life, it can be still preventable. The mostly significant risk factor for FBA is caregivers knowledge lacking. A pre/post quasi design of experimental was implemented in the outgoing study. Three hundred mothers as purposive were included in the current study. The study aim was to assess the supportive strategies influence for mothers in respect to prevention and first aid of mechanical airway obstruction among children. The work was performed in the outpatient pediatric department of El Sayed Galal University hospital. Tool I: data sheet as socio-demographic for children and their mothers, Tool II and Tool III: sheet of questionnaire in respect to knowledge of mothers besides reported practices of mothers. Results showed that the mean age of the studied mothers was (34.13± 8. 97), and more than three quarters of them (%76.7) were didn’t receive previous training program. Differences of significant were detected between post and pre supportive strategy in knowledge of mothers and reporting practices in prevention and first aid of chocking that wasn’t affected by their socio-demographic characteristics (P value ?0. 05).